NEPENTHES NAGA, A NEW SPECIES OF NEPENTHACEAE FROM BUKIT BARISAN OF SUMATRA - Pitra - Akhriadi; Hernawati; Alfindra - Primaldhi; Muhamad - Hambali (BRIN Publishing (Penerbit BRIN), 2009)
AKHRIADI,P.,HERNAWATI, PRIMALDHI, A. & HAMBALI, M. 2009. Nepenthes naga, a new species of Nepenthaceae from Bukit Barisan of Sumatra. Reinwardtia 12(5): 339 – 342. A new species of Nepenthes from North Sumatra is described as Nepenthes naga Akhriadi, Hernawati, Primaldhi & Hambali. The key characters for this species are a triangular dichotomous appendage resembling a snake's tongue inserted sub-apically on the undersurface of the lid, and the undulate lid margin